2005
DOI: 10.1080/00288330.2005.9517396
|View full text |Cite
|
Sign up to set email alerts
|

Decadal temperature changes in the Tasman Sea

Abstract: Ocean temperature changes between 1991 and 2005 in the eastern Tasman Sea were analysed. This area was chosen because of a combination of data availability, low mesoscale variability and because of its importance in determining the climate of the downwind New Zealand landmass. A large warming extending to the full depth of the water column (c. 800 m) was found to have occurred between 1996 and 2002. This warming was seen in measurements by expendable bathythermographs and also in satellite sea surface temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 18 publications
(22 reference statements)
4
41
0
Order By: Relevance
“…South of the TF, circulation in the Tasman Sea has generally been considered to be weak. Sutton et al (2005) showed decadal variability in subsurface temperature in this region ( Fig. 9), but could find no local forcing mechanisms, leading them to conclude that the signal seen in the Tasman Sea is part of a larger South Pacific-wide phenomenon.…”
Section: East Australian Current and Tasman Frontmentioning
confidence: 92%
See 2 more Smart Citations
“…South of the TF, circulation in the Tasman Sea has generally been considered to be weak. Sutton et al (2005) showed decadal variability in subsurface temperature in this region ( Fig. 9), but could find no local forcing mechanisms, leading them to conclude that the signal seen in the Tasman Sea is part of a larger South Pacific-wide phenomenon.…”
Section: East Australian Current and Tasman Frontmentioning
confidence: 92%
“…Sprintall et al (1995) suggested anomalous ocean heat transports in the Tasman Sea may be related to the prolonged ENSO episode that began in early 1991. Sutton et al (2005) documented a large-scale warming extending to at least 800 m in the Tasman Sea between 1996 and 2002, and suggested that the signal seen in the Tasman Sea is part of a larger South Pacific-wide phenomenon.…”
Section: Climate Variability and The Oceansmentioning
confidence: 96%
See 1 more Smart Citation
“… Obtain long time-series of temperature profiles at approximately repeated locations in order to unambiguously separate temporal from spatial variability [54].…”
Section: High Density Transectsmentioning
confidence: 99%
“…The reason behind the maximum in bottom water temperature in 1998-2000 and reduced vertical mixing is probably the unusually warm air temperatures and sea surface temperatures occurring in the region at that time (Sutton et al 2005). Decreased vertical mixing in 1998-2000 has also been observed in other New Zealand lakes (unpubl.…”
Section: Discussionmentioning
confidence: 75%